Thermoluminescence yield of neutron irradiated Gd:Mg-doped silica glass - N.T., Abahreh; S.F., Abdul Sani; S.S., Ismail; Fernando, Laura Elizabeth; N., Tamchek; A. Karim, Julia; K.S., Almugren; Roslan, Nur Adilah; A.S., Siti Shafiqah; D.A., Bradley (Elsevier, 2023)
The thermoluminescence yield of silica glass doped with Gd2O3 and MgO is investigated as a potential material for neutron dose measurement. The dosimetric materials used herein were prepared via the sol-gel route with concentration of rare earth metal oxides varying from 1 to 10 mol%. Reactor irradiations were made at 750 kW thermal power, producing thermal, epi-thermal and fast neutron fluxes of 5.61 × 1012, 2.51 × 1012, 2.58 × 1012 n/cm− 2 .s− 1 , respectively. It has been found that 1 mol% Gd:Mg doped SiO2 exhibits excellent dosimetric response over the entire dose range investigated, obtaining a regression coefficient in excess of 96%. The thermoluminescence (TL) glow curves have been deconvolved, at best fit yielding a total of six peaks, the associated activation energies and frequency factors also being obtained. The results indicate sol-gel Gd:Mg doped SiO2 to offer promising performance as a low-cost passive radiation dosimeter, with utility for both radiotherapy and industrial applications.